Ocena ryzyka kredytowego gospodarstw rolnych z zastosowaniem metody analizy hierarchicznej problemu - Bryndza, Joanna (The use of AHP method in credit risk assessment in agriculture, 2006)
The article describes AHP method, presents possibilities of using this method in credit risk assessment in agriculture. The author builds the hierarchy of criteria. On the basis of surveys carried out on 10 experts’ estimates, the priority of each criterion is obtained using AHP method.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1128, s. 9-23